The role of toll-like receptors 4 in the pathogenesis of anemia of inflammation - Pohribna, A. O.; Погрібна, Анастасія Олександрівна (ДЗ «Запорізька медична академія післядипломної освіти МОЗ України», 2019)
Introduction. Toll-like receptors (TLRs) located on the cytoplasmic membrane are members of the family of signaling pathogen-recognizing receptors, thus realizing the first line of anti-infection protection. Their functions are realized by capturing, processing antigens and presenting processed antigenic peptides in combination with molecules of the main histocompatibility complex. Ligand recognition of TLRs initiates the activation of signaling pathways, resulting in the expression of cytokine genes, antimicrobial peptides and other molecules. Aim of study. To study the role of TLRs4 in the pathogenesis of anemia of inflammation.
Keywords: тези доповідей